Witch Doctors and Battleship Stalkers: The Edges of Exculpation in Entrapment Cases - Preis, John F. (1999)
The bumbling criminal has long been humorous to the law-abiding. Take, for example, a man recently intent on robbing a bank. The man entered a Bank of America bank, grabbed a deposit slip, and wrote on it This iz a stikkup. Put all your muny in this bag. ' While waiting in line for a teller, he became worried that someone had seen him write the note and would inform the police. Thus, he exited the bank, walked across the street to the Wells Fargo bank, and gave the note to a teller. The teller, probably sensing his lack of dangerousness from the note, informed him that she could not comply because the note was on a Bank of America deposit slip, not a Wells Fargo slip. He then returned to the other bank and began to wait in line. The Wells Fargo teller called the police and the man was arrested while waiting in line at the Bank of America.' Many may wonder whether this man had enough wits to be a successful criminal. In general, however, this concern is irrelevant to the law. As long as he had an intent to commit the crime, and acted on that intent, he is culpable, and therefore punishable. There are rare cases, however, where unsuccessful defendants are exonerated. Consider for example a witch doctor who intends to commit murder with a voodoo doll; or an individual who tries to sink a battleship with a BB gun. In such cases, few would argue that prosecution for attempted murder or attempted battleship sinking is appropriate. Although these hypotheticals push the limits of possibility, they highlight the question of whether criminal inability may ever be grounds for exculpation